47. HEALTH STATUS OF WORKERS AT BINH DUONG GARMENT JOINT STOCK COMPANY IN 2024 (Vietnam Journal of Community Medicine, 2025)
Object: This study aimed to describe the health status of workers at Binh Duong Garment Joint Stock Company in 2024.Method: A descriptive cross-sectional study was conducted from May to October 2024, involving all 1673 employees with available health examination records during the year. Data were retrospectively collected from archived medical records. Diseases and health status were classified according to Decision No.1613/QD-BYT.Results: Only 14.9% of workers were classified in health grade I (very good), while 13.2% fell into grades IV and V (poor and very poor health). The majority were in grades II and III (71.9%). Male workers had better health than females, with a higher proportion in grade I (23.8% vs. 9%) and lower proportions in grades IV and V (p < 0.05). Workers aged ≥ 45 and those working overtime had a significantly higher risk of being in poor health (grades IV and V), whereas those with education beyond high school had a lower risk (p < 0.05).Conclusion: The overall health status of workers remains limited, with a considerable proportion classified as having poor health. Interventions are needed to enhance health care, monitoring, and working conditions, especially for female workers, older employees, and those with overtime workloads.
Keywords: Worker health; garment workers; health classification; Binh Duong